Searching for the rate determining step of the H2S reaction on Fe (110) surface - Salawu Omotayo Akande (9904027) (2020)
The adsorption and dissociation of H2S on Fe surface play a key role in carburization condition and a detailed understanding of the kinetics and rate-determining step of this process from an atomistic modeling perspective will help in understanding better ways of mitigating metal dusting. Hence, we employed first-principles density functional theory with a correction for the long-range interactions to investigate H2 reaction on Fe (110) surface. We probed the role of orientation of H2S on adsorption energetics, elementary pathways and dissociation barriers on Fe(110) surface. We report the geometries and energetics of an exhaustive set of molecular and fragmented states induced by the different orientations of H2S on Fe (110) surface. Our investigation further revealed that H2S can be either adsorbed as a molecule, as HS + H, or even as H/S/H atoms depending on the orientation of the molecule and the site of adsorption. In addition, we calculated the rate of adsorption and dissociation to resolve the competition between adsorption sites, and found that the complete decomposition can commence from either the long bridge or short bridge sites. Other Information Published in: Applied Surface Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.apsusc.2020.147470